Prospective study of systemic and mucosal immune responses in dysenteric patients to specific Shigella invasion plasmid antigens and lipopolysaccharides. - Oberhelman, R A (1991)
Shigellosis is a major cause of infant morbidity and mortality in developing countries. To find immunological correlates of specific protection against shigellosis, we examined chronological samples of sera, stool extracts, duodenal aspirates, and saliva samples from 39 adults and 22 children with shigellosis from Peru for the presence of specific antibody to invasion plasmid antigens (Ipa) common to all virulent Shigella strains, by using both a whole-organism enzyme-linked immunosorbent assay (ELISA) and a Western blot (immunoblot) assay. Antibody responses to lipopolysaccharide (LPS) from Shigella serotypes both homologous and heterologous to the infecting strain were also determined by ELISA. ELISAs showed that the highest serum immunoglobulin G (IgG) antibody titers to Shigella whole organisms both with and without surface Ipa were found in adults and malnourished children, the two groups with the shortest and longest durations of disease, respectively. Mucosal IgA antibody titers to Shigella strains decreased over time to a much greater extent than serum IgG titers, and IgA to Ipa in mucosal secretions was found in adults and well-nourished children but not in malnourished children. The presence of mucosal antibody to Ipa may limit the spread and severity of the infection, as indicated by the prolonged illness observed in malnourished children who have no significant mucosal antibody to Shigella Ipa. Serum antibody titers to the Ipa antigens were high relative to anti-Shigella LPS antibody titers, especially in pediatric patients. In contrast to the anti-Ipa responses observed, no differences in antibody responses to LPS in children compared by nutritional status were found. High levels of serum and mucosal cross-reacting antibody to heterologous serotype LPS were found between Shigella flexneri serotypes 1a and 2a. Different patterns of immune response to Ipa proteins and LPS that may aid in the definition of Shigella antigens important in host protection were observed in adults, well-nourished children, and malnourished children.